RoboSantral: An autonomous mobile guide robot - Denker, A.; Dilek, A.U.; Sarioglu, B.; Savas, J.; Gokdel, Y.D. (Institute of Electrical and Electronics Engineers Inc., 2015)
RoboSantral, An autonomous mobile robot which has been designed and realized in order to guide the visitors through a university campus, is presented in this paper. This robot accompanies guests through the campus and gives presentations on predefined locations. Location data is obtained from GPS sensors. Targets such as faculty buildings, museums etc... are recognized by the image processing of pre-defined tags. As microprocessor and microcontroller, Raspberry Pi and Arduino are used respectively. © 2015 IEEE.
2015 IEEE International Conference on Industrial Technology, ICIT 2015 -- 17 March 2015 through 19 March 2015 -- -- 112951
Keywords: Image Processing; Autonomous Mobile Robot; Faculty Buildings; Location Data; Mobile Guide Robots; University Campus; Robots